Pendidikan Anak dalam Perspektif Psikologi Pendidikan Islam - Hartadi Hartadi; Siti Rokhimah (Lembaga Yasin AlSys, 2026)
Although child education has been widely studied from the perspectives of education and developmental psychology, learning orientations that emphasize academic achievement more than spiritual, moral, emotional, and social development remain a fundamental problem. This study aims to analyze the concept of child education from the perspective of Islamic educational psychology, identify the principles of child development, and explain its implications for educational practices in families and educational institutions. This study used a library research method with a qualitative approach. Data were obtained through the review of books, scientific articles, classical Islamic works, and academic documents relevant to educational psychology, child development, and Islamic education. Data analysis was conducted through data reduction, theme categorization, conceptual interpretation, and conclusion drawing. The results showed that child education from the perspective of Islamic educational psychology is based on the concepts of fitrah, tawhid, adab, role modeling, habituation, affection, and the integrated development of intellectual, emotional, social, and spiritual potential. The family functions as the primary educational environment, while schools play a role in strengthening the internalization of values through learning, teacher role modeling, and a religious educational culture. The conclusion of this study affirms that Islamic educational psychology offers a holistic framework for child education oriented toward shaping individuals who are faithful, knowledgeable, morally upright, independent, and responsible. The implications of this study include the importance of integrating Islamic values, developmental psychology, and humanistic learning strategies in curriculum development, strengthening teacher competence, and developing family parenting patterns.